2018
DOI: 10.1186/s40878-018-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Segmented socioeconomic adaptation of New Eastern European professionals in the United States

Abstract: This study examines the socioeconomic adaptation of post-1991 Eastern European professionals in the United States. The data were obtained from the pooled 2006–2010 American Community Surveys. The analysis includes recent immigrants between ages of 25–65 who have at least an associate’s degree. Skilled immigrants in professional or managerial occupations are compared with non-professionals or managers to examine and compare socioeconomic outcomes. The findings presented in this study support the segmented assim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Additionally, researchers and clinicians should consider within-group differences among European American immigrants. As to occupational privileges and income levels, the migratory experience of East European immigrants differs from that of Northern and Western European counterparts with similar educational backgrounds (Michalikova, 2018). East European immigrants indicated that their cultural values were different from the U.S. mainstream values (Adler, 2004: Robila & Krishnakumar, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, researchers and clinicians should consider within-group differences among European American immigrants. As to occupational privileges and income levels, the migratory experience of East European immigrants differs from that of Northern and Western European counterparts with similar educational backgrounds (Michalikova, 2018). East European immigrants indicated that their cultural values were different from the U.S. mainstream values (Adler, 2004: Robila & Krishnakumar, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The decennial Osteopathic Survey of HealthCare in America (OSTEOSURV) is the sole prognosticator for osteopathic recognition in the United States; however, it tends to generalize findings under larger racial categories [ 7 , 11 , 12 ]. As delineated by the American Osteopathic Association (AOA), Eastern European is considered under the “White/Caucasian” umbrella which follows guidelines set by the United States National Library of Medicine [ 13 ]. In comparing this study with previous OSTEOSURV results, there are comparable levels of DO and OMM knowledge; however, much higher rates were found in OSTEOSURV, which may be due to OSTEOSURV respondents primarily based in the United States Midwest, an area that traditionally has high osteopathic recognition due to the historical roots of the osteopathic profession [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors unique to highly educated/skilled migrants that pose barriers to economic integration and workplace participation: the foreign credential recognition process [ 25 , 26 ], occupational mismatches [ 27 , 28 ], hiring chances [ 26 ], and long-term earnings gaps [ 25 , 29 ]. These barriers have been generally attributed to or categorized as ethnic penalties [ 30 , 31 ] and are noticeable in comparison to native citizens. The foreign credential recognition process is complex as it is not standardized across professions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here, Western countries standardize foreign degrees from other Western-identified countries. Michalikova, in her research on Eastern European immigrants, finds that they are hindered by socioeconomic differences based on their educational systems, pre-emigration labor market experiences, and the language barrier [ 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%